Experiences of Living with Fat Bodies with Stigma in Poland. An Intersectional Analysis Based on Biographical Interviews - Bielska, Beata; Wójtewicz, Anna; Mańkowska, Katarzyna (Qualitative Sociology Review, 2023)
The article offers an analysis of living with a fat body and ways of experiencing it in everyday life in the context of stigmatization of this type of corporality. Biographical interviews with fat people of varying socio-demographic profiles were conducted. The analyses show that having a fat body/being fat is generally a stigma that discredits the individual in the eyes of the so-called normals based on both physical characteristics and character traits allegedly associated with fatness. The participants mainly medicalize and internalize the stigma of fatness and manage it specifically by passing, covering, and coming out. In transgender people, fatness may never take on the characteristics of a stigma, but instead allows the individual to obscure another stigma or conform to social expectations of appearance in line with the gender identity.